Evaluation of sample quality by non-destructive and destructive methods. - Tanaka, Hiroyuki (Asean Engineering Journal)
Effects of sample disturbance on the undrained shear strength were investigated from samples with various qualities, retrieved by different types of samplers at the Takuhoku site, Sapporo, Japan. Sample disturbance, caused by difference in sampling tube geometry, was evaluated by two nondestructive methods : measurement of residual effective stress (p r) by ceramic disc; and shear wave velocity (Vs) and thus maximum shear modulus (Gbe), by bender element. Sample quality was also evaluated by three types of destructive test, i.e. shear tests : unconfined compression, fall cone and triaxial recompression tests. Geometry effects of the sampling tube, for example, thickness of the tube wall, edge angle, and existence of a piston were carefully examined. It was found from these studies that the small edge angle of a tube sampler is important to obtain high quality sample. In addition, the existence of a piston does not have a significant effect on the strength properties.